MARKETING ANALYSIS OF BOGOR TARO (Colocasia Esculenta) IN CIPELANG VILLAGE SUB-DISTRICT CIJERUK - BOGOR DISTRICT - Assegaff, Alifah Rahma; Buhari, Ahmad; Setiawan, Johan (Management Science Research Journal, 2022)
Bogor district is one of the production centers of taro tubers in Indonesia. One of the biggest taro producers in the Bogor district area is the Cijeruk sub-district. Cipelang Village is a village that has the largest taro tubers production in the Cijeruk sub-district. As taro producers in Cipelang Village, farmers should get maximum profit from taro sales and marketing. But, there is a considerable price difference between the price received by farmers and the price paid by consumers. Therefore, an analysis is needed regarding the channels that are suitable for use by farmers in taro marketing. This study aims to analyze marketing channels, costs, margins, profit marketing, function and role of the marketing agency, and efficiency marketing. Based on research, there are two marketing channels in Cipelang Village. Channel 1 (farmers-consumers) and channel 2 (farmers-collectors-retailers-consumers). The total costs for channel 1 Rp. 100/tuber and channel 2 is Rp. 850/tuber. The total marketing margin for channel 1 is Rp. 8,000/tuber and channel 2 is Rp. 17,000/tuber. The total profit for channel 1 is Rp. 7,900/tuber and for channel 2 is Rp. 16,150/tuber. The marketing functions used are exchange, physical, and facility functions. The research data concludes that the first channel is more efficient than the second one because it has a lower technical efficiency value than the second. As well as having a greater economic efficiency value compared to the second marketing channel